Plant Systems Biology at the Single-Cell Level. (November 2017) - Libault, Marc; Pingault, Lise; Zogli, Prince; Schiefelbein, John
Abstract : Our understanding of plant biology is increasingly being built upon studies using 'omics and system biology approaches performed at the level of the entire plant, organ, or tissue. Although these approaches open new avenues to better understand plant biology, they suffer from the cellular complexity of the analyzed sample. Recent methodological advances now allow plant scientists to overcome this limitation and enable biological analyses of single-cells or single-cell-types. Coupled with the development of bioinformatics and functional genomics resources, these studies provide opportunities for high-resolution systems analyses of plant phenomena. In this review, we describe the recent advances, current challenges, and future directions in exploring the biology of single-cells and single-cell-types to enhance our understanding of plant biology as a system. Trends: To enhance our understanding of plant cells as systems, there is a need to emphasize studies on individual cell types and individual cells of plants. The systems biology of plant single-cell-types and single-cells requires the development of new methodologies to collect biological information and new computational tools to enhance the integration of these data sets. The establishment of advanced strategies to isolate and identify distinct cells comprising the plant is needed to reveal cellular heterogeneity, cell–cell communication, and signaling networks in plant biology. The comparative analysis of plants at the level of the single-cell will enhance interspecies comparisons by avoiding complications due to variation in tissue or organ anatomy. Many plant mutants have been characterized based on developmental and physiological defects. The biology of single-cell-types or single-cell systems applied to mutant plant cells should reveal molecular networks controlling cell-specific physiological and developmental processes in plants.